An alternative LC-UV procedure for the determination of prochloraz residues in fruits - Navickiene, Sandro; Ribeiro, Maria Lúcia [UNESP] (FapUNIFESP (SciELO), 2005)
An alternative method using liquid chromatography with UV detection for the determination of prochloraz as 2,4,6-trichlorophenol in mango, papaya and orange is described. Ethyl acetate, acetone and dichloromethane were tested for extraction of prochloraz from the fruits. After extraction the residue of prochloraz was derivatized with pyridine hydrochloride. The analysis was carried out using liquid chromatography with UV detection and gas chromatography with electron-capture detection. Average recoveries of prochloraz from spiked fruits (0.1 and 0.2 mg kg-1) ranged from 80% to 94% with relative standard deviations between 5.6% and 12.6% (n=8). Detection and quantification limits were 0.05 and 0.1 mg kg-1, respectively. The LC-UV method was applied to mango and papaya samples submitted to dip treatment with a prochloraz formulation under laboratory conditions. In addition, fruit samples obtained from local markets were analysed. ©2005 Sociedade Brasileira de Química.
Keywords: Derivatization; Food analysis; Fruit; Fungicides; Pesticides; Prochloraz; fungicide; analytic method; derivatization; electron capture detection; extraction; food analysis; liquid chromatography; mango; papaya; quantitative analysis; ultraviolet spectroscopy